Emergence of KPC‐producing Klebsiella pneumoniae in Uruguay: infection control and molecular characterization. Issue 3 (4th April 2014) - Marquez, C.; Ingold, A.; Echeverría, N.; Acevedo, A.; Vignoli, R.; García‐Fulgueiras, V.; Viroga, J.; Gonzalez, O.; Odizzio, V.; Etulain, K.; Nuñez, E.; Albornoz, H.; et al.
Abstract We describe the first outbreak of Klebsiella pneumoniae carbapenemase‐producing K. pneumoniae (KPC‐KP), the infection control measures adopted and the shift in resistance patterns of isolates during antibiotic treatment. The ST258 KPC‐KP strain exhibited a multiresistant antibiotic phenotype including co‐resistance to gentamycin, colistin and tigecycline intermediate susceptibility. Isolates before and after treatment had different behaviour concerning their antibiotic susceptibility and the population analysis profile study. A progressive increase in the aminoglycosides (acquiring amicacin resistance) and β‐lactam MICs, and a decreased susceptibility to fosfomycin was observed throughout the administration of combined antimicrobial regimens including meropenem. A high meropenem resistance KPC‐KP homogeneous population (MIC 256 Jg/mL), could arise from the meropenem heterogeneous low‐level resistance KPC‐KP population (MIC 8 Jg/mL), by the selective pressure of the prolonged meropenem therapy. The kpc gene was inserted in a Tn4401 isoform a, and no transconjugants were detected. The core measures adopted were successful to prevent evolution towards resistance dissemination.